Development, validation and field evaluation of a quantitative real-time PCR able to differentiate between field Mycoplasma synoviae and the MS-H-live vaccine strain. Issue 4 (4th July 2017) - Dijkman, R.; Feberwee, A.; Landman, W. J. M.
ABSTRACT: A quantitative PCR (qPCR) able to differentiate between field Mycoplasma synoviae and MS-H vaccine strain was developed, validated and evaluated. It was developed using nucleotide differences in the obg gene. Analytical specificity and sensitivity assessed using DNA from 194 M. synoviae field samples, three different batches of MS-H vaccine and from 43 samples representing four other avian Mycoplasma species proved to be 100%. The detection limit for field M. synoviae and MS-H vaccine strain was 10 2-3 and 10 2 colony-forming units PCR equivalents/g trachea mucus, respectively. The qPCR was able to detect both, field M. synoviae and MS-H vaccine strain in ratios of 1:100 determined both using spiked and field samples. One hundred and twenty samples from M. synoviae- infected non-vaccinated birds, 110 samples from M. synoviae- vaccinated birds from a bird experiment and 224 samples from M. synoviae negative (serology and PCR) birds were used to determine the relative sensitivity and specificity using a previously described M. synoviae PCR as reference. The relative sensitivity and specificity for field M. synoviae were 95.0% and 99.6%, respectively, and 94.6% and 100% for the MS-H-live vaccine, respectively. Field validation and confirmation by multi locus sequence typing revealed that the qPCR correctly distinguished between MS-H and field M. synoviae . Evaluation of the differentiating M. synoviae qPCR in three commercial flocks suggested transmission of MS-H-live vaccine from vaccinated to non-vaccinated flocks at the same farm. Furthermore, it showed evidence for the colonization with field M. synoviae in MS-H-vaccinated flocks.